PERANCANGAN SISTEM REKOMENDASI POLA HIDUP SEHAT BAGI PERESIKO ASAM URAT - Bayu Hartono (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2024)
Gout is caused by several things, one of which is the consumption of foods high in purine, choosing the right food menu for all foods consumed is an obligation... apart from this, there are various other factors that can increase the risk of this disease, namely increasing age and male gender, family health history, obesity, consumption of certain medications, certain medical conditions, unhealthy lifestyles and injuries due to surgery. The low priority given by health services to non-communicable diseases and inadequate public knowledge. Gout is a public health problem in Indonesia and is still not fully addressed. Knowledge and assistance regarding the right food to consume is a solution in overcoming this problem. For this reason, the authors in this study developed an expert system as a reference for gout risk to improve healthy lifestyle patterns. This system was developed with 2 benefits, namely getting recommendations and monitoring uric acid levels. As a result of the tests carried out, it is known that from a health practitioner's point of view, the system developed is suitable for use to accompany prevention and monitoring activities for gout sufferers and the information regarding the patient's dietary history presented by the system can be used as evaluation material during control. Users strongly agree with the system created due to lack of knowledge and lack of control in consuming foods that cause gout.